2013
DOI: 10.1186/1749-8090-8-36
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment for traumatic thoracic aortic pseudoaneurysm: a case report

Abstract: Cases of an endovascular treatment for traumatic aortic injury are extremely rare. A prompt diagnosis of traumatic thoracic aortic pseudoaneurysm through a 3-dimensional computed tomographic angiography of aorta and emergency repair are mandatory to rescue the life-threatening condition. An endovascular treatment is a trend for traumatic aortic injury because of lower invasivity, morbidity and mortality. We reported a rare case of traumatic aortic injury with thoracic aortic pseudoaneurysm definitively diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The existing data on the incidence of grade III thoracic aorta injury is scanty due to the low caseload, its myriad clinical presentations and is restricted to the published literature, in the form of case reports and case series, which report an incidence of 1–10%. The most common presenting problems are chest pain, fever and shortness of breath 2 3…”
Section: Discussionmentioning
confidence: 99%
“…The existing data on the incidence of grade III thoracic aorta injury is scanty due to the low caseload, its myriad clinical presentations and is restricted to the published literature, in the form of case reports and case series, which report an incidence of 1–10%. The most common presenting problems are chest pain, fever and shortness of breath 2 3…”
Section: Discussionmentioning
confidence: 99%
“…Among the available treatment options, endovascular intervention stands as a viable choice. In the immediate aftermath of endovascular intervention for these patients, there exists a range of short-term complications including stroke, paraplegia, complications at the puncture site, device collapse, and damage to the recurrent laryngeal nerve [ 4 ]. It is noteworthy, however, that there is a dearth of comprehensive data concerning long-term complications [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although normal chest radiography does not exclude rupture, some studies have indicated that patients with blunt injury to the aorta may present with a normal mediastinum on chest radiography. However, chest radiography will reveal key diagnostic signs, such as widening of the mediastinum, left-sided hemothorax, trachea shifting to the right, left apical cap sign, and sternal, scapular, or rib fractures, all of which are suggestive symptoms of blunt aortic rupture [9] . This is necessary, especially in medical centers that do not yet have CTA scanning facilities.…”
Section: Discussionmentioning
confidence: 99%